2020
DOI: 10.3390/ijms21175972
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNAs in Hematopoiesis with a Focus on Acute Myeloid Leukemia and Myelodysplastic Syndrome

Abstract: Circular RNAs (circRNAs) constitute a recently recognized group of noncoding transcripts that function as posttranscriptional regulators of gene expression at a new level. Recent developments in experimental methods together with rapidly evolving bioinformatics approaches have accelerated the exploration of circRNAs. The differentiation of hematopoietic stem cells into a broad spectrum of specialized blood lineages is a tightly regulated process that depends on a multitude of factors, including circRNAs. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 93 publications
(146 reference statements)
0
2
0
Order By: Relevance
“…The hypothesis of circRNAs interfering with MDS pathophysiology was supported by the observation that exogenous inhibition of the spliceosome components, commonly affected by MDS mutated genes, can cause an imbalance between circular and linear RNA concentrations within affected cells towards overexpression of the circular molecules [94,95]. Wedge et al recently reported that specific cancer-associated circRNAs, such as circZNF609 and circCSNK1G3, are upregulated in MDS patients with U2AF1 mutations compared to unmutated controls [96].…”
Section: Circular Rnasmentioning
confidence: 99%
“…The hypothesis of circRNAs interfering with MDS pathophysiology was supported by the observation that exogenous inhibition of the spliceosome components, commonly affected by MDS mutated genes, can cause an imbalance between circular and linear RNA concentrations within affected cells towards overexpression of the circular molecules [94,95]. Wedge et al recently reported that specific cancer-associated circRNAs, such as circZNF609 and circCSNK1G3, are upregulated in MDS patients with U2AF1 mutations compared to unmutated controls [96].…”
Section: Circular Rnasmentioning
confidence: 99%
“…One of the earliest studies to describe circRNAs in hematopoiesis was published in 1998 by Caldas et al (47) in which they introduced splicing of the MLL gene, a frequently rearranged gene in a variety of hematological malignancies, which is involved in a complex process that results in the formation of abnormal transcripts with different genomic orientation, scrambled transcripts, and circRNAs in both normal and leukemic cells. Research on hematopoiesis-related circRNAs has grown rapidly since NGS emerged, and the catalog of these circRNAs has dramatically expanded (48). For example, it is known that circ-BACH1 (exons 2-4) is mainly expressed in hematopoietic stem cells (HSCs) and multipotent progenitors (MPPs), whereas circ-FNDC3B (exon 5-6) is broadly expressed in natural killer (NK) cells, circ-ELK4 (exon 4-3), circ-SLFN12L (exon 2-3) and circ-MYBL1 (exon 12-7) are preferentially expressed in T cells and NK cells, circ-AKT3 and circ-CCDC91 were found to be expressed across lymphoid cells (49).…”
Section: The Roles Of Circrnas In Leukemiamentioning
confidence: 99%
“…Noncoding RNAs are emerging regulatory factors for myelopoiesis, including lncRNAs (Qiu et al 2021 ) and circRNAs (Dostalova Merkerova et al 2020 ). In addition, many microRNAs have been found to be regulators or effectors of myelopoietic transcription factors (Kim et al 2019 ).…”
Section: Using Zebrafish To Explore the Regulation Of Myelopoiesismentioning
confidence: 99%